Virtual Subjects of Knowledge: Information Challenges on the Hypertext - Ana Marcela Mungaray Lagarda (Universidad Autónoma de Baja California, 2005)
This article presents a reflection on the virtual subject inside the theory of knowledge and the challenges of the information poured in the hiper-text. The discussion is nourished around the need or shortage of a structure of knowledge set against a structure of information that, at the same time, confronts our academic tasks and reconfigures our strategies to transmit knowledge. This exercise was made from a direct non-participant observation of Internet users in auto-access public and institutional centers. The studied population was a group of students in out of school activity who were using Internet searching for topics related to "research", "tasks" or only "to know more" about something.